1992
DOI: 10.1177/009365092019004005
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Vocal Communication Between Young Adults and Their Parents and Grandparents

Abstract: This study examined characteristics of young adult children's vocal communication with parents and grandparents. Seven young adult women telephoned their parents and grandparents, had a brief conversation with them, and described a collage to them. Voice samples of the conversations were rated by groups of 12-15 male and female judges on scales reflecting vocal qualities and interpersonal attitudes. Judges also guessed with whom the speakers were talking. Finally, collage descriptions were coded for message co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Stereotypic beliefs about the elderly are mainly negative, including physical, cognitive, and interpersonal deficiencies (see Montepare & Zebrowitz, 2002;Pasupathi, Carstensen, & Tsai, 1995;Zebrowitz & Montepare, 2000). The interaction with an aged person is often characterized by the adoption of an oversimplified and patronizing language (Caporael, 1981;Caporael, Lucaszewski, & Culbertson, 1983; see also Montepare, Steinberg, & Rosenberg, 1992). In a related way, elder adults are less likely to be provided with important information than young adults (Rubin & Brown, 1975) and are also less likely to receive adequate medical treatment (Butler, 1975;Grant, 1996;Hillerbrand & Shaw, 1989).…”
Section: The Perception Of Elderly Adultsmentioning
confidence: 99%
“…Stereotypic beliefs about the elderly are mainly negative, including physical, cognitive, and interpersonal deficiencies (see Montepare & Zebrowitz, 2002;Pasupathi, Carstensen, & Tsai, 1995;Zebrowitz & Montepare, 2000). The interaction with an aged person is often characterized by the adoption of an oversimplified and patronizing language (Caporael, 1981;Caporael, Lucaszewski, & Culbertson, 1983; see also Montepare, Steinberg, & Rosenberg, 1992). In a related way, elder adults are less likely to be provided with important information than young adults (Rubin & Brown, 1975) and are also less likely to receive adequate medical treatment (Butler, 1975;Grant, 1996;Hillerbrand & Shaw, 1989).…”
Section: The Perception Of Elderly Adultsmentioning
confidence: 99%
“…Other work shows that as people age, communication with strangers can involve stereotypical and unsatisfying conversations (Giles, Coupland, Coupland, Williams, & Nussbaum, 1992;Ryan, 1994). Under certain circumstances, even close others engage in ageist communication with older adults (Baltes & Wahl, 1992;Montepare, Steinberg, & Rosenberg, 1992). This latter body of work implies that audiences for later life remembering may be less than optimally supportive and responsive.…”
Section: Autobiographical Remembering As a Developmental Process Impomentioning
confidence: 99%
“…Understanding this communicative relationship may help us to better understand children's attitudes toward all elders (Nussbaum & Bettini, 1994), and with elders' increased life expectancy, more individuals may have contact with grandparents for a longer time. Montepare, Steinberg, and Rosenberg (1992) asked 40 young adults, ages 18 to 20, to telephone their parents and grandparents, and after a warm-up conversation period, to describe a collage of pictures of different people. Results indicated that, although the young adults' content did not become less complex, their voices became higher, louder, and more feminine sounding when conversing with grandparents than with parents.…”
Section: Familymentioning
confidence: 99%